Michigan State Universty Dry Bean Breeding Program - Kelly, James D. (1989)
The dry bean breeding program at MSU is focused on the development of high yielding, upright, disease resistant cultivars with improved canning quality in eight commercial classes of dry bean. The research work is an ongoing investigation where genetic stocks at different stages of development exist in all commercial classes and new varieties are released after adequate testing. As different needs appear or as disease or quality problems arise, the program looks to address these by incorporating new genetic sources. The major focus for this current research is to develop high-yielding, anthracnose resistant navy and black bean varieties; identify high-yielding, disease-resistant bush and vine cranberry varieties; continuation of a study of root rot resistance in kidney beans; development of an upright, disease-resistant pink bean; combine genes for rust, virus, anthracnose and white mold resistance in pinto and great northern market classes to ensure the successful production of all new MSU varieties in Michigan.